2010
DOI: 10.5539/ijbm.v6n1p283
|View full text |Cite
|
Sign up to set email alerts
|

Does the Food Advertisement on Television Have the Impact on Children’s Food Purchasing Behavior? A Study Based on Pakistan Food Advertisement

Abstract: The purpose of conducting this study was to examine television advertisements and children's food using pattern when they were watching television and their desire to purchase goods that they saw advertisements on television. This study was conducted in two parts. In the first part, content analysis of the television advertisements was conducted. In second part of the study, a questionnaire was given to 200 parents. Total of 75 of these parent's children were attending 1st, 2nd and 3rd grades of the primary sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Moreover, the amount of time children spend watching TV was associated with the number of their requests for advertised foods, and the likelihood that parents would purchase these foods. [6,8] This nding may be a reason for a previous conclusion that longer TV viewing time was associated with a higher intake of energy and fat among children. [6] Simultaneously, the current study found that children who purchased advertised foods had higher protein intake, which may be due to the ads of milk and dairy products targeted to children.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, the amount of time children spend watching TV was associated with the number of their requests for advertised foods, and the likelihood that parents would purchase these foods. [6,8] This nding may be a reason for a previous conclusion that longer TV viewing time was associated with a higher intake of energy and fat among children. [6] Simultaneously, the current study found that children who purchased advertised foods had higher protein intake, which may be due to the ads of milk and dairy products targeted to children.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have found that TV food ads increased children's requests and purchases for advertised foods and parents' purchases of advertised foods. [6][7][8][9][10] Gbadamosi et al found that TV ads were relevant to children's consumption of goods and services, prompting children to request advertised products or brands, particularly advertised foods, from their parents in Africa. [7] This nding indicated that TV ads can in uence children's food preferences and purchase requests.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, various research on television advertising and consumer purchasing patterns was conducted by various academics. Separately examined in these studies was the effect of television advertising on consumer purchasing behavior (Haroon et al, 2010;Ansari & Joloudar, 2011). Studies have shown that television advertisements have the most substantial effects on viewers, convincing them to begin purchasing and significantly impacting how customers perceive products (Ansari & Joloudar, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers had done similar studies to analyse the positive or a negative impact of food advertisements on the behaviour of children (Roberts and Pettigrew, 2007; Morgan et al , 2008; Harron et al , 2011). The findings show that such commercials have a negative effect on children’s eating habits.…”
Section: Literature Reviewmentioning
confidence: 99%